PENGARUH EKSTRAK DAUN CENGKEH (SYZYGUM AROMATIC) TERHADAP KUALITAS DEDAK PADI SELAMA PENYIMPANAN - Lily Joris; Shirley Fredriksz; Fadly I. Siyono (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2021)
Rice Bran is an important feeding material because it contains high nutrition that are necessary for livestock to live and reproduce. However, it contains high amount of fat around 10-14%, which cause it to easily emits putrid odor. That is why, it is necessary to preserve the rice bran. The purpose of this research is to find out the effect of clove leaves extract on rice bran’s physical quality during storage. This could be used as the primary data in utilizing clove leaves as preservatives. This research uses a Completely Randomized Design and descriptively analyzed in the Feed Technology and Engineering Laboratory of Unpatti’s Faculty of Agriculture in the period of two month. The ingredients that are used in this research are rice bran, and clove leaves extract with different level of usage. There are 4 different trials with 4 repetitions. The variables that are observed is the physical quality of the bran, including: weight, color, odor, numbers of fleas, and weather it builds up mold or not. The result of this research showed that the use of clove leaves extract with 2 : 1 ratio gave better result for physical quality of the rice bran, because it could suppress the number of flea, and eliminate musty odor of rice bran in storage period of one month.